Thread/Warp - Blonski Campos Cruz; Jenny Logico Cruz (Body, Space & Technology Journal, 2022)
Thread/Warp was an online durational performance that investigated into the idea of stamina amidst our performance-obsessed, techno-contemporary world. Performed live on July 14 in a span of 12 hours via Zoom (and occasionally streamed via Facebook Live), Thread/Warp featured two performers in separate screen windows as they navigated the spectacle and exploitation of their bodies in two intersecting spaces: 1) the confines and confidentiality of their private domestic space(s); and 2) the expansive and exposing nature of the public space via their relationship with the video cameras.  Thread/Warp sought to explore what it meant to sustain energy, tenacity, resilience, and patience—especially in a climate wherein we are relentlessly expected to perform beyond what’s necessary; to tirelessly create infinite yet exhausted spectacles of both our physical and virtual bodies; and to constantly amplify our human stamina in order to brutally compete with the stamina of technology itself. To put the concept into methodical exploration, this project utilized the concept of space as a crucial stimulus in conditioning one’s body to perform beyond what’s necessary. Specifically, the project took into account two spaces that had radically shaped our relationship with stamina —the private and the public—no longer as two distinct and separate entities, but rather as spheres that constantly intersect, overlap, blur, and at times even trade with one another. Thread/Warp examined the shifting conditions of the private domestic space—from a supposed place of rest and rejuvenation to a place of perpetual labour and recycled productions—and how these unprecedented changes either deflate or escalate our stamina. Secondly was the method on public space, in which the project investigated how public exposure (via Zoom and Facebook Live) radically maneuvered our sense of stamina, and how this further warped and manipulated our relationship with rest, recuperation, production, performance, labour, and ultimately, individual purpose and meaning. By considering the interjections of the private and public space, the project explored how this further affected tremendous change in the dynamic, potency, and frailty in the performer’s body.